Bioherbicidal Activity and Metabolic Profiling of Potent Allelopathic Plant Fractions Against Major Weeds of Wheat—Way Forward to Lower the Risk of Synthetic Herbicides - Anwar, Sobia; Naseem, Saadia; Karimi, Saira; Asi, Muhammad Rafique; Akrem, Ahmed; Ali, Zahid (Frontiers in Plant Science, 2021)
The productivity of major field crops is highly compromised due to weed infestation. Inefficient weed management practices, and undue and excessive use of chemical herbicides have drastically contaminated the environment and human health, in addition to resistance development in weed species. Therefore, utilization of allelopathic plants to explore phytochemicals, as potent organic alternatives to such chemical herbicides has become indispensable. The current study evaluates the comparative bio-herbicidal potential of methanolic extracts of castor (Ricinus communis), artemisia (Artemisia santolinifolia), wheat (Triticum aestivum) and sorghum (Sorghum bicolor) to suppress growth of major weeds i.e., wild mustard (Sinapis arvensis), Italian ryegrass (Lolium multiflorum) and carrot grass (Parthenium hysterophorus). The results demonstrated a concentration dependent effect on weeds’ growth. Overall, in-vitro seed germination was reduced from 60% to 100% in response to 5% (w/v) extracts concentration. Significant reduction in radicle length, hypocotyl length and fresh biomass of the weeds was also observed. A strong inhibitory effect was seen in in-vivo pot experiments, revealing that application of 10 to 20% methanolic extracts induced permanent wilting and substantial reduction in chlorophyll content of weeds along with 20 to 80% increase in oxidative stress. Artemisia showed most significant allelopathic effect, on account of highest phenolic and flavonoid contents, followed by castor, wheat and sorghum, against S. arvensis, L. multiflorum and P. hysterophorus respectively. Phytochemical analysis, through High Performance Liquid Chromatography (HPLC), also exhibited a correlation between extract’s phytotoxicity and their antioxidant potential due to their major constituents (rutin, quercetin, catechin, gallic acid, vanillic acid, syringic acid, ferulic acid, p-hydroxy benzoic acid, p-coumaric acid and sinapic acid), among the total of 13 identified in methanolic fractions. Comprehensive profiling of allelochemicals with liquid chromatography–mass spectrometry (LC–MS) determined 120, 113, 90 and 50 derivates of phenolic acids, flavonoids and alkaloids, reported for the first time through this study, demonstrating significant allelopathic potential of the targeted plant fractions which can be explored further, to develop a sustainable bio-herbicidal formulation.